PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN IPAS MATERI EKOSISTEM KELAS III SD NEGERI 4 BANDAR DUA - Musfirah, Putri; Mislinawati; Suci Fitriani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Low students’ learning outcomes in IPAS learning on ecosystem material are indicated by students’ achievement that has not yet met the Criteria for Learning Achievement (KKTP). This condition is influenced by the learning process that is still dominated by the teacher and the use of less varied learning models, resulting in students’ limited active involvement in discovering learning concepts. This study aims to determine the implementation of the Discovery Learning model and students’ learning outcomes in IPAS learning on ecosystem material for grade III students at SD Negeri 4 Bandar Dua. This study employed a quantitative approach with a descriptive research design. The research subjects were grade III students of SD Negeri 4 Bandar Dua, while the research objects were the implementation of the Discovery Learning model and students’ learning outcomes. Data were collected through learning outcome tests and observation. The obtained data were analyzed using descriptive statistical analysis to describe students’ learning outcomes after the implementation of the Discovery Learning model. The results of the study show that the implementation of the Discovery Learning model led to improvements in students’ learning outcomes in IPAS learning on ecosystem material. Students demonstrated more active involvement in the learning process, particularly during the stages of observing, identifying problems, and independently discovering concepts. Overall, the implementation of the Discovery Learning model in IPAS learning on ecosystem material for grade III students at SD Negeri 4 Bandar Dua can be considered an alternative learning model that encourages students’ activeness and conceptual understanding.